INTEGRASI PENDIDIKAN KARAKTER ISLAM MELALUI AI CHATBOT DALAM PEMBELAJARAN PAI PADA GENERASI ALPHA - M. Kemal Ardhan Al Hamd; Iffa Fauziyah; Akhsani, Wigati; Naelum Minatika; Ilham Bintang; Rodianto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to analyze the integration of AI Chatbot in Islamic character education within Islamic Religious Education (PAI) for Generation Alpha in the digital era. The research uses a qualitative method with a library research approach that focuses on the study and analysis of various scientific literatures related to the utilization of artificial intelligence technology in Islamic education. The research data sources consist of primary and secondary data obtained from journal articles, books, academic documents, and relevant official websites. Literature search was conducted thru reputable scientific databases such as Google Scholar, Garuda, and Sinta with a publication range of 2016–2026, resulting in 21 scientific journals, 5 news articles, and 4 books that align with the research focus. The data was documented thru a literature review, considering inclusion and exclusion criteria. Data were analyzed using content analysis techniques reinforced thru Focus Group Discussions (FGD). The research results indicate that the use of AI Chatbot in PAI learning is conceptually relevant and has the potential to support the internalization of Islamic character values such as adab, amanah, sidq, tabayyun, muraqabah, ihsan, and akhlak karimah in Generation Alpha. Based on the literature review, AI Chatbot shows promise as an interactive learning medium capable of enhancing accessibility, flexibility, and student interest in PAI material. However, this study also identifies various limitations such as the potential for AI hallucination, information bias, validity of Islamic sources, student data privacy risks, and ethical challenges in the use of digital technology. Therefore, teachers still hold a central position as content verifiers, value guides, moral exemplars, and ethical controllers of AI usage in PAI learning. Thus, AI Chatbot is more appropriately positioned as a supportive learning medium, rather than the primary determinant of the success of Islamic character education for Generation Alpha.